Characterizations of Cuprous Oxide Thin Films Prepared by Sol-Gel Spin Coating Technique with Different Additives for the Photoelectrochemical Solar Cell - D. S. C. Halin; I. A. Talib; A. R. Daud; M. A. A. Hamid (International Journal of Photoenergy)
Cuprous oxide (Cu2O) thin films were deposited onto indium tin oxide (ITO) coated glass substrate by sol-gel spin coating technique using different additives, namely, polyethylene glycol and ethylene glycol. It was found that the organic additives added had a significant influence on the formation of Cu2O films and lead to different microstructures and optical properties. The films were characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), and ultraviolet-visible spectroscopy (UV-Vis). Based on the FESEM micrographs, the grain size of film prepared using polyethylene glycol additive has smaller grains of about 83 nm with irregular shapes. The highest optical absorbance film was obtained by the addition of polyethylene glycol. The Cu2O thin films were used as a working electrode in the application of photoelectrochemical solar cell (PESC).